THE ORIGIN OF SULFIDE-RIMMED METAL GRAINS IN ORDINARY CHONDRITES - Lauretta D.S.; Lodders K.; Fegley B.; Kremser D.T. (My University, 1997)
We report results from an experimental study of sulfide chemistry during metamorphism on ordinary chondrite parent bodies. Artificial LL-chondrite material, composed of silicate, iron metal, and sulfide grains, was placed in sealed, evacuated silica tubes and heated to either 500°C or 900°C. These temperatures are representative peak metamorphic temperatures experienced by type 3 and type 6 ordinary chondrites, respectively. Rapid sulfur mobilization occurs during heating and results in the formation of sulfide rims around the metal grains and sulfur loss from the original sulfide crystals. The newly formed sulfide rims have two distinct layers that incorporate nearby silicate grains. We also observe narrow sulfide trails that follow silicate grain boundaries and connect separate sulfide-rimmed metal grains. The morphologies of the sulfide rims suggest that vapor transport is the main mechanism for sulfur mobilization. Sulfur loss is observed along cracks and crystal boundaries of the initial sulfide grains. After extensive reaction, patches of iron metal appear at the outer edges of the sulfide crystals and large pore spaces form throughout the original sulfides. The experimental metal-sulfide assemblages resemble those found in low metamorphic grade ordinary chondrites. This suggests metamorphism is mainly responsible for the observed metal-sulfide textures in these chondrites.
Keywords: METALS; TROILITE; PYRRHOTITE; ORDINARY CHONDRITES; METAMORPHISM